Analisis Pengaruh Kualitas Produk dan Strategi Pemasaran Instagram terhadap Keputusan Pembelian Yourdayflower Bouquet Kecamatan Bangkinang Kota - Rahmad Akbar; Yetti, Dzulhijjah; Nofiar.Am, Andri; Perdana, M. Alkadri; Nurkholis; Habibie, Indra (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
This study aims to analyze the influence of product quality and Instagram marketing strategies on purchasing decisions for bouquets at Yourdayflower Bouquet, Bangkinang Kota District. The data collection methods used in this study are questionnaires and documentation. Data analysis was conducted quantitatively using multiple linear regression tests. Based on the partial test results (T-test), Instagram marketing strategies have a significant influence on bouquet purchasing decisions at Yourdayflower Bouquet. Meanwhile, the simultaneous test results (F-test) indicate that product quality and Instagram marketing strategies collectively impact purchasing decisions. The findings of this study confirm that both product quality and digital marketing strategies through Instagram play a crucial role in increasing consumer attraction and influencing their decision to purchase bouquets at Yourdayflower Bouquet. Therefore, optimizing digital marketing strategies and improving product quality can be strategic steps to enhance sales